THE IMPACT OF TECHNOLOGY ACCEPTANCE MODEL ON BEHAVIORAL INTENTION OF INTERNET BANKING USERS IN MANADO - Pandei, Liane Jeanet (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Internet Banking is described as an approach to performing financial services over mobile communications technology. It enables banking clients to perform a diverse range of financial services including checking account balances, linking of accounts, inter- and intra-transfer of funds, payment of bills, Internet purchases, and resetting of password. Through the use of Internet Banking, clients are able to conduct banking services anywhere and anytime by means of a mobile device, tablet or mobile phone. The purpose of this research is to find the impact of technology acceptance model toward behavioral intention on internet banking user. This research used quantitaitve method. The sample of this research is 100 person. This research used purposive sampling and the date filled by the questionaire. The result is Perceived Usefulness and Perceived Ease-of-Useas the independent variable simultaneously affect Behavioral Intention as the dependent variable, Perceived Usefulness as one of independent variables does not partially affects Behavioral Intention significantly, Perceived Ease-of-Use as one of independent variables does not partially affects Behavioral Intention significantly.Keywords: technology acceptance model